The Impact of Organizational Commitment, Remuneration, and Work Loyalty on Employee Performance in the Education Office of North Labuhanbatu Regency - Treisna, Panca; Hasbalnikistan, Muhammad Yusuf; Djunaidi, Fathia Ukhti; Hasibuan, Ikhwan Sahbana; Munthe, Erwin; Riana, Zeni (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to analyze the influence of organizational commitment, remuneration, and work loyalty on employee performance at the North Labuhanbatu Regency Education Office. Using a quantitative method through a survey of 110 employees, the data was analyzed using multiple linear regression. The results of the study show that organizational commitment, remuneration, and work loyalty significantly affect employee performance. Job loyalty has the strongest influence compared to other variables. The determination coefficient (R²) of 67.8% shows that these three variables explain most of the variations in employee performance. These findings underscore the importance of increasing job loyalty, a fair remuneration system, and organizational commitment to improving employee performance in the public sector.